Vandalized Texts: Soft Power Potential - O. V. Kruzhkova; M. R. Babikova; S. D. Robin (Научный диалог, 2024)
Considering the increased pollution of urban spaces by vandalistic transformations, it is important to take into account the impact they have on observers. The aim of this study is to identify the potential of “soft power” in vandalized texts by determining the characteristics of their perception and memorization, taking into account the theme of the text and the linguistic device used to attract attention. The study utilizes 21 photo images of vandalized texts recorded in the urban environment of major cities in the Russian Federation, which were used as stimulus material. The research is based on the examination of the perception and memorization of vandalized texts through a laboratory experiment using an eye-tracker (sample size — 20 individuals). It was found that 19 to 67% of vandalized texts are remembered upon single exposure (13 seconds). Political texts exhibit the highest memorability, while creolized texts based on language play receive positive evaluation. The most vulnerable to the potential of “soft power” in vandalized texts is the immersive eye-catching strategy of respondents. The authors conclude that vandalized texts are easily remembered, attracting the observer’s attention through unique linguistic devices in text organization.